An atom probe study of fine scale structure in AlMgSi(Cu) alloys - Vaumousse, D; Cerezo, A; Warren, P; Court, SA (2002)
The 6xxx series (AlMgSi(Cu)) aluminium alloys are currently being used for automotive body sheet applications in which the in-service strength of the body panel is achieved through age hardening during the automotive paint bake cycle (typically in the range 170-200 degreesC for times of up to 30 minutes). It has been shown that preageing treatments in the range 50-120 degreesC may improve the subsequent ageing response, causing the material to reach peak hardness more rapidly during paint-baking.In the present work, the precipitate microstructure evolution in AlMgSi(Cu) alloys during preageing has been studied using 3-dimensional atom probe (3DAP) microanalysis. The effect of quenching and preageing followed by natural ageing on the microstructure evolution in Cu-containing and Cu-free 6xxx alloys have been studied by 3DAP analysis. Dedicated software has been developed to automatically detect clusters of solute atoms within the volume of 3DAP microanalysis. This allows better quantification of precipitate parameters such as shape, composition, number density, and volume fraction. Hardness measurements have also been performed to link the mechanical properties to the microstructural information.